Serum ferritin and the risk of short-term mortality in critically ill patients with chronic heart failure: a retrospective cohort study - Zhou, Zijing; Yang, Deyi; Li, Chan; Wu, Ting; Shi, Ruizheng (Frontiers in Physiology, 2023)
Background: Serum ferritin levels are associated with a higher risk of incident heart failure (HF). Whether serum ferritin levels, either increased or decreased, predict the risk of mortality in individuals with chronic HF (CHF) is unknown.Objectives: This study aimed to clarify the potential predictive significance of serum ferritin levels in assessing the short-term mortality in critically ill patients with CHF.: Critically ill patients with CHF were identified from the Multiparameter Intelligent Monitoring in Intensive Care Database III and IV (MIMIC III and IV) databases. Linear and logistic regression model and Cox proportional hazards models were applied to assess the associations between serum ferritin and survival.Results: A total of 1,739 and 2,322 CHF patients from the MIMIC III and IV databases, respectively, fulfilled the inclusion criteria. In the MIMIC III group, compared with the reference group (serum ferritin ≥ 70 and < 500 ng/mL), serum ferritin ≥ 1000 ng/mL was a significant predictor of 28-day (odds ratio [OR], 1.76; 95% confidence interval [CI], 1.14-2.72) and 90day mortality (OR, 1.64; 95% CI, 1.13-2.39). The results from the Cox regression and Kaplan-Meier curves revealed similar results. In the MIMIC IV group, serum ferritin ≥ 1000 ng/mL was a significant predictor of inhospital (OR, 1.70; 95% CI, 1.18-2.46), 28-day mortality (OR, 1.83; 95% 3 CI, 1.24-2.69) and 90-day mortality (OR, 1.57; 95% CI, 1.11-2.22) after adjusting for confounding factors.High ferritin levels (≥ 1000) ng/mL were associated with increased short-term mortality in critically ill patients with CHF, indicating that serum ferritin may be a useful prognostic marker for CHF.